2018
DOI: 10.1111/nph.15079
|View full text |Cite
|
Sign up to set email alerts
|

Mapping xylem failure in disparate organs of whole plants reveals extreme resistance in olive roots

Abstract: The capacity of plant species to resist xylem cavitation is an important determinant of resistance to drought, mortality thresholds, geographic distribution and productivity. Unravelling the role of xylem cavitation vulnerability in plant evolution and adaptation requires a clear understanding of how this key trait varies between the tissues of individuals and between individuals of species. Here, we examine questions of variation within individuals by measuring how cavitation moves between organs of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
125
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 71 publications
(97 reference statements)
9
125
1
Order By: Relevance
“…It should also be noted that caution must be exercised when comparing the vulnerabilities of leaves and stems, as it is possible that plant organs have different degrees of resistance to cavitation. Variation in the vulnerability of different plant organs was shown in several early studies in conifers and angiosperms (Kavanagh, Bond, Aitken, Gartner, & Knowe, ; Sperry & Ikeda, ; Sperry & Saliendra, ; Zimmermann, ) and in more recent studies in olive plants (Rodriguez‐Dominguez, Carins Murphy, Lucani, & Brodribb, ), grape vines (Charrier et al, ), and trees (Johnson et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…It should also be noted that caution must be exercised when comparing the vulnerabilities of leaves and stems, as it is possible that plant organs have different degrees of resistance to cavitation. Variation in the vulnerability of different plant organs was shown in several early studies in conifers and angiosperms (Kavanagh, Bond, Aitken, Gartner, & Knowe, ; Sperry & Ikeda, ; Sperry & Saliendra, ; Zimmermann, ) and in more recent studies in olive plants (Rodriguez‐Dominguez, Carins Murphy, Lucani, & Brodribb, ), grape vines (Charrier et al, ), and trees (Johnson et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…Our results identify dynamic root hydraulic conductance during water stress as an important driver of early stomatal closure in olive plants. Our novel hydraulic method allowed us to observe sharp declines in whole root K , including the soil–root interface, occurring over the same range of water potentials as stomatal closure, far above those required to trigger xylem cavitation (Torres‐Ruiz et al ., ; Rodriguez‐Dominguez et al ., ). Our findings indicate that the most important changes in the hydraulic system of these olive plants during moderate water stress did not occur in leaves or stems, and did not involve cavitation.…”
Section: Discussionmentioning
confidence: 97%
“…This allowed us to determine the contribution of each hydraulic component to the whole plant resistance, identifying the important and dynamic role of the hydraulic pathways from the soil to the root as a primary factor reducing whole plant K within the sensitive water potential range of stomatal function. Furthermore, the finding that K root did not change within a range of ψ stem down to < −4 MPa also confirmed previous results indicating a high resistance to cavitation in the coarse roots of olive (Rodriguez‐Dominguez et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Rodriguez‐Dominguez et al . () found roots of Olea europaea saplings to have more resistant xylem than stems and leaves, and Tsuda & Tyree () reported higher hydraulic safety in roots compared with stems in A. saccharinum saplings. In contrast, several studies indicated fine roots to exhibit low hydraulic safety and thus to act as hydraulic ‘fuses’ (Jackson et al ., ; Cuneo et al ., ).…”
Section: Discussionmentioning
confidence: 99%